Pengembangan Media Flashcard Dalam Meningkatkan Kemampuan Kognitif Anak Pada Pembelajaran Bahasa Indonesia Kelas 1 Minu Tri Bhakti At-Taqwa - Hasna Raisa Fitri; Muh Ngali Zainal Makmun; Fadilah, Lutfi (Berkala Ilmiah Pendidikan, 2024)
This research began with the lack of learning media used to improve cognitive abilities, so it was necessary to develop a product in the form of flashcards as a learning media. This research aims to determine the development process of learning media, and to determine the effectiveness of flashcard media as a learning media in improving cognitive abilities.The research methodology used is research and development (R&D), with the borg and gall model, which includes 10 steps however researchers only used 7 development steps namely: 1) potential and problems 2) data collection 3) product design 4) design validation 5) design revision 6) product trials 7) product revisions. The results of this research show that flashcard media obtained an average percentage score from media experts of 96% with very feasible criteria, and from material experts a percentage of 78.0% with fairly valid criteria. The response from students was also very good, as evidenced by the achievement of cognitive indicators including: students were able to name letter symbols, students were able to write their own names, students were able to remember the material presented by the teacher, students were able to apply the material that had been presented. by the teacher. This shows that the flashcard media that researchers have developed is suitable for use as learning media.